2021
DOI: 10.1029/2020jb020074
|View full text |Cite
|
Sign up to set email alerts
|

Equation of State of TiN at High Pressures and Temperatures: A Possible Host for Nitrogen in Planetary Mantles

Abstract: Nitrogen (N) is cosmochemically abundant (Burbidge et al., 1957) and is the dominant component of the Earth's atmosphere, yet the transport and storage of N within the planet's deep interior is still relatively unexplored in comparison to other volatile species (Johnson & Goldblatt, 2015). Geochemical studies have constrained the evolution of Earth's nitrogen-rich atmosphere by reconstructing past environments (Marty, 2012; Marty & Dauphas, 2003) through geologic measurements and models. Experimental studies h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
(159 reference statements)
0
3
0
Order By: Relevance
“…Experiments performed in diamond anvil cells [ 102 ] demonstrated that Fe–N compounds can be stable at extremely high temperatures and pressures corresponding to the conditions of Earth's core. Other experiments also demonstrated the stability of titanium nitride, iron nitride and carbonitride from deep upper mantle to core pressure [ 103–105 ]. These results indicate that nitrogen is siderophile at high P – T and reducing conditions, that nitrogen can be stored as nitride in Earth's deep mantle, and that nitrogen is a potential light element in Earth's core (Fig.…”
Section: Earth's Nitrogen Budget and Speciationmentioning
confidence: 99%
“…Experiments performed in diamond anvil cells [ 102 ] demonstrated that Fe–N compounds can be stable at extremely high temperatures and pressures corresponding to the conditions of Earth's core. Other experiments also demonstrated the stability of titanium nitride, iron nitride and carbonitride from deep upper mantle to core pressure [ 103–105 ]. These results indicate that nitrogen is siderophile at high P – T and reducing conditions, that nitrogen can be stored as nitride in Earth's deep mantle, and that nitrogen is a potential light element in Earth's core (Fig.…”
Section: Earth's Nitrogen Budget and Speciationmentioning
confidence: 99%
“…Using generalized gradient approximation [1] high-pressure effects on lattice volume, Bulk modulus, and phonon density of state have been studied up to the pressure of 50Gpa. Using diamond anvil cell and X-ray diffraction method the EoS and stability of this compound have been measured up to the pressure of nearly 70 GPa and temperature of 2700 K [4] and up to pressure of 94GPa [5]. Based on the first principle approximation, the elastic constants, Debye temperature, and bulk modulus of this material, were investigated at high temperatures as well as high pressures [6].…”
Section: Introductionmentioning
confidence: 99%
“…Its ceramic has a tendency to resist corrosion. Spreading barriers is one of its uses, as is in some superconducting devices [1]. Due to TiN's useful characteristics, such as their high hardness, superior corrosion resistance, heat resistance, and great wear resistance, among others, titanium nitride (TiN) coatings have a wide range of uses [2].…”
Section: Introductionmentioning
confidence: 99%